The literary appropriation of science - Aguinaldo, Dennis Andrew S. (UP Los Baños Journal, 2012)
At the University of the Philippines Los Baños (UPLB), the challenge is to provide platforms for the fields of literature and science to engage in order to evolve interdisciplinary and critical frames of thinking. The postmodern fiction of Bartheleme presents possibilities for such convergence. This article analyzes the strategies of three of his stories and analyzes their strategies of appropriating elements from the nature and social sciences. In "Bunny Image, Loss of the Case of Bitsy S." Barthelme shuffles the images and grammar of psychiatry, philosophy, popular culture and the sex industry. He showcases ways of playing with the names of people and diseases: name-dropping, truncation, and the double bind. An inventory of effects reveals a complex underlying order that resonates with the overaching theme of loss. "Report" offers a stylized interview regarding technology's role in war. In the story, the chief engineer's surreal catalouges of technological achievements qualify as aesthetic instances of a long-running debate currently labeled under transhumanism and posthumanism. Finally, "At the End of Mechanical Age" features a unique hybridization of Biblical and technological geneses. Through hyperbolejuxtaposiyion, anachronism and metafiction. Barthelme narrates the fate of lovers keenly conscious of time and the illusions that humanity conjures about it in order to survive it. The process of such conjuration involve subdividing time into periods, naming past, present, and future and metaphorizing the unknown. Through these interpretations and their attendant recommendations, the article lays open social science, natural sciences, and technology to the literary intentions of UPLB teachers and students.